The Relationship Between Religiosity and School Engagement in Female Students At Wustho Level at Darussalam Islamic Boarding School Martapura - Silmia, Indah; Mayangsari, Marina Dwi; Safitri, Jehan (Jurnal Kognisia, 2023)
Awareness in carrying out religious activities cannot be separated from the level of development of each individual. By understanding the religious values, people will apply the values in everyday life, like when they study. When studying, one needs to be engaged in studying so that what is learned can be practiced well. Engagement can be understood as the extent to which a student actively participates in learning activities. This study aims to investigate the relationship between religiosity and school engagement in female students at the wustho level at Darussalam Islamic Boarding School, Martapura. The sample was 110 female students at the level of wutsho at Darussalam Islamic Boarding School, Martapura. The scales consisted of the scales of religiosity (cronbach's alpha = 0.909) and school engagement (cronbach's alpha = 0.861). The hypothesis was tested using the Pearson product moment correlation test. The results of data analysis indicate the acceptance of the alternative hypothesis (Ha) and the rejection of the null hypothesis (H0). The results of the correlation test showed a value of 0.189, with the effective contribution of the relationship between the two variables of 3.6%. It can be concluded that the relationship between religiosity and school engagement was very low.